(3fbO GdTYQs - (3bOGeI Hf LYaQ Hf bOGeI Hf RjGO GdHZOGOj, CHh GdaQL,J (B337 (3g` s
(3ChdgG (B:s
(3bGd CHh GdahM bOGeI Hf LYaQ GdYde HGdTYQ jfbSe CbSGekG abSe jfSH Edi Yde YQhV hhRfg hbSe jfSH Edi Yde bhGajg hebGWYI hbSe jfSH Edi Yde ZQjHI s
(3BNQgG (B:s
(3adjS fSHI gPG GdTGYQ Gddg YR hLd Edi Cfg QH ghO HCLhO ef fSHJg Edi Cfg QH fhM hdcf GdbGajI cGfJ OGdjg aCJi HPdc ddSLY dG dEaGOI eYfi HeG CJi efg hGddg CYde Je GdcJGH s
(3fSNJGfs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B191 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B128s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdCOHs